Evaluasi Peraturan Daerah Kota Surabaya Nomor 7 Tahun 2002 tentang Pengelolaan Ruang Terbuka Hijau di Taman Prestasi Kota Surabaya - Rachman, Novia Ayu Dwi; Indartuti, Endang; Rukminingsih, Nunuk (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
According to the Local Regulation of the City of Surabaya No.7 of 2002 about the Management of Green Open Space relating to the management of maintaining facilities that already exist in Green Open Space (GOS), such as in Taman Prestasi. The statement of the problem of this study is "How is the Evaluation Policy of Local Regulation of the City of Surabaya No. 7 of 2002 about the Management of Green Open Space in Taman Prestasi Surabaya?". It applies descriptive qualitative research method. There were also informants who provided information related to this study, namely the Head of the Sub-Section of the City Park UPTD in DKRTH, and the visitors of Taman Prestasi. For data collection techniques, this study uses interview, observation, and documentation. By analyzing this study,Â  we know that the Regional Regulation of Surabaya City No. 7 of 2002 is considered to provide benefits to society especially the visitors of Taman Prestasi and run according to the regulations of the Surabaya City Government. The results of this study discuss the Policy Evaluation of William N. Dunn which has three indicator; firstly achievement of objectives, secondly effective, responsive, and fair carried out by implementing agencies, and lastly outputs and Results resulting from policy implementation.Keywords: Evaluation Policy, Taman Prestasi, Outcome